1991
DOI: 10.1093/sleep/14.5.419
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Eating Disorders: Polysomnographic Correlates of a Heterogeneous Syndrome Distinct from Daytime Eating Disorders

Abstract: Over a 5-yr period, 19 adults presented to our sleep disorders center with histories of involuntary, nocturnal, sleep-related eating that usually occurred with other problematic nocturnal behaviors. Mean age (+/- SD) at presentation was 37.4 (+/- 9.1) yr (range 18-54); 73.7% of the patients (n = 14) were female. Mean age of sleep-related eating onset was 24.7 (+/- 12.9) yr (range 5-44). Eating occurred from sleep nightly in 57.9% (n = 11) of patients. Chief complaints included excessive weight gain, concerns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
180
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 0 publications
0
180
0
2
Order By: Relevance
“…1 SRED has been found associated with various sleep disorders in case series: sleepwalking (SW), periodic limb movements during sleep (PLMS), narcolepsy, restless legs syndrome (RLS), and obstructive sleep apnea (OSA). 6,7 The high rate of PLMS and rhythmic masticatory muscle activity in SRED patients, 8 together with the high prevalence of SRED (33%) in idiopathic RLS, 9 suggests a pathophysiological derangement of the dopaminergic system. Besides SRED, other compulsive behaviors can arise from nocturnal sleep, such as nocturnal smoking (NS).…”
mentioning
confidence: 99%
“…1 SRED has been found associated with various sleep disorders in case series: sleepwalking (SW), periodic limb movements during sleep (PLMS), narcolepsy, restless legs syndrome (RLS), and obstructive sleep apnea (OSA). 6,7 The high rate of PLMS and rhythmic masticatory muscle activity in SRED patients, 8 together with the high prevalence of SRED (33%) in idiopathic RLS, 9 suggests a pathophysiological derangement of the dopaminergic system. Besides SRED, other compulsive behaviors can arise from nocturnal sleep, such as nocturnal smoking (NS).…”
mentioning
confidence: 99%
“…The polysomnographic recordings showed that D.L. 's eating episodes arose from stage 2 sleep which may differ from eating episodes that arise from,delta sleep and which have been associated with somnambulism (28). D.L.…”
Section: Discussionmentioning
confidence: 93%
“…Oswald and Adam (25) described night-eating episodes in a normal-weight male which were correlated with periods of rapid eye movement (REM) sleep. Schenck et d. (28) reported on 19 adults who presented to a sleep disorders center with histories of involuntary nocturnal sleep-related eating. In this group, most of the sleep-related eating disorders were controlled by treating the underlying sleep disorder with pharmacological agents.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it can not be ruled out that eating disorders or eating anomalies might manifest at some point in the life of narcoleptic patients, eg, at the time of onset and then ameliorate or disappear. In addition, the (parasomnic) sleep related eating disorder (Schenck et al 1991) and the night eating syndrome are not covered by the SIAB, so that the potential contribution to increased BMIs of these disorders could not be evaluated. Both traits are not known to be necessarily associated with obesity or increased BMIs in general (Schenck et al 1993;Striegel-Moore et al 2006) but may play a role in subsets of obese persons or under specifi c circumstances such as in narcolepsy.…”
Section: Discussionmentioning
confidence: 99%